2022
DOI: 10.3390/biomedicines10112959
|View full text |Cite
|
Sign up to set email alerts
|

Levels of TNF-α and Soluble TNF Receptors in Normal-Weight, Overweight and Obese Patients with Dilated Non-Ischemic Cardiomyopathy: Does Anti-TNF Therapy Still Have Potential to Be Used in Heart Failure Depending on BMI?

Abstract: Background. We sought to measure the levels of adipokines, TNF-α and soluble receptors (sTNFr1, sTNFr2) in heart failure patients with reduced ejection fraction (HFrEF) due to non-ischemic cardiomyopathy (nDCM). Methods. A total of 123 patients with HFrEF due to nDCM were divided into three groups according to BMI: 34 (27.6%) normal weight, 56 (45.5%) overweight and 33 (26.8%) obese. A six-minute walk test, echocardiography and right heart catheterization were performed. Serum concentrations of adiponectin, le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 83 publications
0
1
0
1
Order By: Relevance
“…The combination of high levels of TNF-α with epithelial cell injury may lead to airway remodeling: a common feature of asthma. Several studies have found circulating concentrations of TNF-α to be elevated in obesity [ 22 , 23 ]. Vieira et al [ 24 ] report that elevated collagen levels in the lungs of OVA-challenged C57BL/6 mice were reduced by anti-TNF-α treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of high levels of TNF-α with epithelial cell injury may lead to airway remodeling: a common feature of asthma. Several studies have found circulating concentrations of TNF-α to be elevated in obesity [ 22 , 23 ]. Vieira et al [ 24 ] report that elevated collagen levels in the lungs of OVA-challenged C57BL/6 mice were reduced by anti-TNF-α treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Также уровни рецепторов sTNFr1 и sTNFr2 коррелировали с уровнем СРБ, но только в группе пациентов с нормальным весом, тогда как для уровней самого лиганда ФНО-α статистически значимых различий получено не было. В этом аспекте интересным является мнение авторов работы о перспективности исследования сывороточных уровней рецепторов sTNFr1 и sTNFr2 в качестве биомаркеров воспаления, ассоциированных с ожирением, у больных с дилатационной неишемической кардиомиопатией, а также в качестве предикторов эффективности лечения перед назначением анти-ФНО терапии [36].…”
Section: биомаркеры воспаленияunclassified